Analisis Tindak Tutur dalam Wacana Iklan Gadaiku by Hartadinata Abasi pada Media Sosial Instagram - Nurhidayah, Nurhidayah; Pafilay, Dian; Apriani, Dini; Ade Riyanto, Andra; Asyhar, Mochammad (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to examine speech acts in advertising discourse on the Instagram account Gadaiku by Hartadinata Abasi using a qualitative approach. Amid the rapid development of the digital era, Instagram has become one of the main social media platforms facilitating interactive two-way communication, enabling users not only to receive information but also to respond, comment, and instantly share content. Various features such as Stories, Reels, and IGTV provide creative opportunities for businesses to reach a wide audience, especially in Indonesia, which had around 103 million active users at the beginning of 2025. The data collection techniques in this study include reading, non-participant observation, and note-taking on Instagram posts from the May 2025 edition. The analysis identified three types of speech acts: locutionary (9 data), illocutionary (15 data), and perlocutionary (9 data), totaling 33 data points. Locutionary acts are used to convey information literally and factually, such as explanations or direct statements. Illocutionary acts function to invite, motivate, advise, or offer solutions to influence the audience’s attitudes or behaviors, while perlocutionary acts aim to elicit certain effects or responses from the audience, such as encouraging real action, building trust, or creating emotional engagement. The findings of this study demonstrate that the speech act strategies employed in Instagram advertisements are effective in building persuasive and interactive communication with today's digital audience. The varied use of speech acts allows advertising messages to be not only informative but also capable of building emotional connections, motivating, and encouraging the audience to act according to marketing objectives. This marks a significant shift from traditional media to digital media, where interactivity, audience segmentation, and flexible content formats become key advantages in modern marketing communication strategies.